Ideomotor perceptions to facilitate technical skills mastering process in football - Smolentseva, V. N.; Khamzin, A. F. (Theory and Practice of Physical Culture, 2017)
Objective of the study was to test feasibility and efficiency of a variety of psychological tools to facilitate the key technical skills being mastered by junior football players. The educational experiment was performed at the Irtysh CYORSS in Omsk city with 9-year-old football players being sampled for the experiment. The subjects were evenly split up into Study and Reference Group of 13 athletes each, with their progress under the experiment being tested by expert progress ratings and special tests. The experimental training model included special psychological tools geared to help the trainees clearly visualize in their minds the right images and focus and keep their internal attention on them to maintain the ideomotor perceptions of the ideal technical skills and apply them to facilitate the skills mastering process and step up the execution quality.